Microreactors to Measure Solubilities in the CO2-H2O-NaCl System. (July 2017) - Caumon, Marie-Camille; Dubessy, Jean; Robert, Pascal; Benaissa, Boubaker
Abstract: The production of experimental data for CO2 solubilities in the H2 O-CO2 -NaCl is of first importance to constraint thermodynamic modelling of CO2 geological storage. Here a mcirocapillaries device is coupled to a Raman microspectrometer to measure CO2 solubility as a function of pressure, temperature and NaCl concentration. The results show an excellent correlation with the equation of state of Duan and Sun [1] and with previous works [2] .